2014
DOI: 10.5146/tjpath.2014.01233
|View full text |Cite
|
Sign up to set email alerts
|

Goblet cell carcinoid of the appendix: a case report

Abstract: Goblet cell carcinoid of the appendix is a rare neuoroendocrine tumor that possesses histological features of both adenocarcinoma and neuoroendocrine tumor. Goblet cell carcinoid of the appendix is more aggressive than conventional neuroendocrine tumors. Here we report a case of a 54-year-old woman with goblet cell carcinoid tumor in the appendix Key Words: Neuroendocrine tumors, Carcinoid, Goblet cell, Appendix ÖZApendiksin goblet hücreli karsinoidi, adenokarsinom ve nöroen-dokrin tümörün histolojik özellikle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This patient was re-operated upon where right hemicolectomy was undertaken (underwent second stage procedure). Older age seems to be associated with GCC, where mean age of GCC patients is around 52 years [24], and others have reported appendicular GCC in two females (60 and 54 year olds) and a male (>60 years) [25], [26], [27], [28]. Although a case of 31-year-old man has also been described in the literature [29].…”
Section: Discussionmentioning
confidence: 99%
“…This patient was re-operated upon where right hemicolectomy was undertaken (underwent second stage procedure). Older age seems to be associated with GCC, where mean age of GCC patients is around 52 years [24], and others have reported appendicular GCC in two females (60 and 54 year olds) and a male (>60 years) [25], [26], [27], [28]. Although a case of 31-year-old man has also been described in the literature [29].…”
Section: Discussionmentioning
confidence: 99%
“…While five-year survival is between 50%-80% for the disease when limited to the appendix, it is less than 20% in the presence of distant metastases[16]. In the literature, it is reported that an appendectomy should be sufficient for the treatment of tumors smaller than 1 cm that do not have no serious mesoappendix involvement and a low Ki-67 index[4,20-22]. …”
Section: Discussionmentioning
confidence: 99%